Detailed experimental and numerical characterization of turbulent flow in components of a water treatment plant - Ragessi, Ivan Matias (2019)
This paper presents a detailed characterization of turbulence in the incoming flow to the clarification component of a water treatment plant, ?Los Molinos? (Córdoba, Argentina). The main problems were related to the presence of turbulent flow patterns throughout the treatment, affecting the proper development of the physical processes required for water clarification. Namely: (a) a poor hydraulic design that could produce a non-homogeneous spatial distribution of the flow, recirculation zones and flow stagnation, and a non-uniform discharge distribution among the sedimentation units as a result of different cross-sectional dimensions of the transverse-channel, and (b) high turbulence intensity that affect the flocs´ size as well as the efficiency of the settling tanks and filters. Firstly, a detailed in-situ experimental characterization of the turbulent flow was undertaken. An acoustic Doppler velocimeter (ADV) was used to characterize the flow turbulence, whereas for discharge measurements and mean flow velocity field an acoustic Doppler current profiler (ADCP) was employed. Secondly, a numerical model, based on the Reynolds-averaged Navier?Stokes (RANS) equations and the k-e turbulence closure model, was validated with the experimental data. Finally, based on the results, a diagnosis and recommendations were made for the optimization of the hydraulic design of the water treatment plant.